2018
DOI: 10.1002/sce.21448
|View full text |Cite
|
Sign up to set email alerts
|

Taking an escape hatch: Managing tension in group discourse

Abstract: Problem solving in groups can be rich with tension for students. This tension may arise from conflicting approaches (conceptual and/or epistemological) and/or from conflict emerging in the social relations among group members. Drawing on video records of undergraduate students working collaboratively, we use three cases to illustrate the multifaceted ways in which conflict arises—combining conceptual, epistemological, and socioemotional dynamics—and a specific way of managing the tension that can emerge from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 88 publications
1
27
0
Order By: Relevance
“…Thus, attending the organizational factors and culture is important, as it sets the stage for changes in instructional practices to be sustained. In addition, theories of organizational learning can still provide insight into these more local phenomena, for instance by shedding light on interpersonal interactions in the study of teams (Sohr, Gupta, & Elby, 2018). For all of these reasons, there is a great value in applying organizational learning theories to the realm of science education.…”
Section: Significancementioning
confidence: 99%
“…Thus, attending the organizational factors and culture is important, as it sets the stage for changes in instructional practices to be sustained. In addition, theories of organizational learning can still provide insight into these more local phenomena, for instance by shedding light on interpersonal interactions in the study of teams (Sohr, Gupta, & Elby, 2018). For all of these reasons, there is a great value in applying organizational learning theories to the realm of science education.…”
Section: Significancementioning
confidence: 99%
“…However, as an increasing number of studies reported the success of the collaborative inquiry approach, more researchers started to pay attention to the factors that contribute to successful collaboration. Besides the emphasis on the content itself, many studies began to focus on the emotion and stress that occurred during the group process, including methods learners used to cope with tension and conflict due to group arguments (Lamminpää & Vesterinen, 2018;Sohr, Gupta, & Elby, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…An important part of this discourse takes the form of relational work, which also includes caring for others involved in the discourse, 21 friendship, 22 and emotion work. 23 Our critique here is similar to Sandra Harding's critiques of the inherent masculinity of the discourse of a "pure mathematics." Harding argued that even the disciplinary value of mathematical axioms, which by definition do not need mathematical proof and cannot be proven mathematically, is determined socially and contextually as other mathematicians apply the axioms in different contexts to advance their mathematical proofs and arguments.…”
Section: Countering Pedagogical Homogeneity and Disciplinary Masculinitymentioning
confidence: 68%